DUAL EDUCATION SYSTEM IN HIGHER EDUCATION: INTERNATIONAL EXPERIENCES, EFFECTIVENESS, AND THE CONTEXT OF UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
This article provides an in-depth scientific analysis of the theoretical and practical foundations of the dual education system and explores the effective methods of its implementation in developed countries, as well as the potential for its broad and systematic application in Uzbekistan's higher education system. Dual education is an innovative pedagogical model that integrates theoretical knowledge with practical skills, preparing students for effective adaptation to the demands of the modern labor market. The article thoroughly examines successful experiences in integrating dual education into higher education and vocational training processes in leading countries such as Germany, Switzerland, Austria, and Singapore. In these countries, dual education enables students not only to gain theoretical knowledge but also to develop practical skills in real working environments, thereby enhancing their professional competencies, critical and independent thinking, and analytical abilities. The article also analyzes the socio-economic significance of introducing dual education into Uzbekistan’s higher education system, its close link with ongoing educational reforms, and its role in aligning with the modern labor market's demands. It considers the opportunities of dual education in improving education quality, preparing students for real work activities, and promoting youth employment, along with pedagogical, organizational, and economic challenges that may arise in the process and potential solutions. Special attention is given to pedagogical innovations, modern educational technologies, and the importance of practical training, including the need for improving teacher qualifications, aligning curricula with labor market needs, and establishing effective cooperation between industry and educational institutions.